Temperature and humidity index (THI) affects salivary cortisol (HC) and dehydroepiandrosterone (DHEA) concentrations in growing bulls following stress generated by performance test procedures - Giaretta, Elisa; Mongillo, Paolo; Da Dalt, Laura; Gianesella, Matteo; Bortoletti, Martina; Degano, Lorenzo; Vicario, Daniele; Gabai, Gianfranco (Frontiers in Veterinary Science, 2023)
The hypothalamus-pituitary–adrenal axis response to a challenge was proposed for genetic selection of robust and resilient animals. As ACTH (adrenocorticotropic hormone) test and hormone measurements in blood may result impractical, it may be useful to measure salivary hormones in response to natural stressors, after an accurate biological validation, to control factors that could contribute to the response. We evaluated whether animal handling during performance test affects salivary HC and DHEA secretion and could be used for selection. We tested the effects of habituation to repeated handling and THI as putative bias. Bull calves (N = 273) undergoing performance test were sampled at 8–9 and 11–13 months (N = 101), 8–9 months (N = 131), or 11–13 months (N = 41). On each test day (D0), calves were isolated, conducted to a squeeze chute and immobilized for 6 min. Saliva samples were collected in the morning after feed administration (T0), and after 6 min immobilization in the squeeze chute (T1) for HC and DHEA measurement. Environmental temperature and relative humidity were recorded every hour from 1:00 h to 24:00 h during the 6 days before the performance test and on D0. Salivary HC and DHEA concentrations were higher in T1 (p < 0.01), although a clear individual positive response to handling could be observed in less than 10% of subjects. The mixed model revealed: (i) HC and HC/DHEA were higher in Young bulls (p < 0.05). (ii) The time of T0 sample collection significantly affected DHEA (p < 0.01) and HC/DHEA (p < 0.05). (iii) THI affected both steroids (p < 0.001) but not HC/DHEA. Spearman correlations suggested that THI weakly affected salivary HC at T0 only (ρ = 0.150, p < 0.01), while moderate statistically significant correlations were found between DHEA and THI at T0 (ρ = 0.316, p < 0.001), and T1 (ρ = 0.353, p < 0.001). Salivary HC and DHEA in response to handling procedures might identify subpopulations of subjects with sensitive HPA axis. Habituation to repeated handling played a role, as the hormone response was lower in older animals. Chronic exposure to high THI had a minor effect on salivary HC visible at T0. A more intense THI effect was observed on salivary DHEA concentrations at both T0 and T1, which should be worth of further investigations.